Larval breeding sites of Lutzomyia longipalpis (Diptera: Psychodidae) in visceral leishmaniasis endemic urban areas in Southeastern Brazil. - Cláudio Casanova; Maria T M Andrighetti; Susy M P Sampaio; Maria L G Marcoris; Fernanda E Colla-Jacques; Angelo P Prado (Public Library of Science (PLoS), 2013)
BACKGROUND: The scarcity of information on the immature stages of sand flies and their preferred breeding sites has resulted in the focus of vectorial control on the adult stage using residual insecticide house-spraying. This strategy, along with the treatment of human cases and the euthanasia of infected dogs, has proven inefficient and visceral leishmaniasis continues to expand in Brazil. Identifying the breeding sites of sand flies is essential to the understanding of the vector's population dynamic and could be used to develop novel control strategies. METHODOLOGY/PRINCIPAL FINDING: In the present study, an intensive search for the breeding sites of Lutzomyia longipalpis was conducted in urban and peri-urban areas of two municipalities, Promissão and Dracena, which are endemic for visceral leishmaniasis in São Paulo State, Brazil. During an exploratory period, a total of 962 soil emergence traps were used to investigate possible peridomiciliary breeding site microhabitats such as: leaf litter under tree, chicken sheds, other animal sheds and uncovered debris. A total of 160 sand flies were collected and 148 (92.5%) were L. longipalpis. In Promissão the proportion of chicken sheds positive was significantly higher than in leaf litter under trees. Chicken shed microhabitats presented the highest density of L. longipalpis in both municipalities: 17.29 and 5.71 individuals per square meter sampled in Promissão and Dracena respectively. A contagious spatial distribution pattern of L. longipalpis was identified in the emergence traps located in the chicken sheds. CONCLUSION: The results indicate that chicken sheds are the preferential breeding site for L. longipalpis in the present study areas. Thus, control measures targeting the immature stages in chicken sheds could have a great effect on reducing the number of adult flies and consequently the transmission rate of Leishmania (Leishmania) infantum chagasi.